Logical error

  • Thread starter topu87
  • Start date
4
0

Main Question or Discussion Point

plz tell me where is the error here-
1 = [tex]\sqrt{}1[/tex] = [tex]\sqrt{}(-1) (-1)[/tex] =[tex]\sqrt{}-1[/tex] [tex]\sqrt{}-1[/tex] = i[tex]^{}2[/tex] = -1

so we get 1= -1. what is the error here?
 

Answers and Replies

4
0
sorry look at this form. This is more understandable than the previous one
1= [tex]\sqrt{1}[/tex] = [tex]\sqrt{(-1) (-1)}[/tex]= [tex]\sqrt{-1}[/tex][tex]\sqrt{-1}[/tex] = i i = i[tex]^{2}[/tex] = -1
 
arildno
Science Advisor
Homework Helper
Gold Member
Dearly Missed
9,946
130
The error lies in the assumption that the square root operation when performed on negative (or in general complex) numbers follow exactly those laws valid when you restrict square rooting to positive numbers.

It just doesn't.
 
51
0
Did you want to say that we can't apply the laws for square-rooting of positive no. to this situation? Plz explain details. What is the exact logic to give in this situation?
 
CRGreathouse
Science Advisor
Homework Helper
2,817
0
Did you want to say that we can't apply the laws for square-rooting of positive no. to this situation? Plz explain details. What is the exact logic to give in this situation?
[tex]\sqrt{ab}=\sqrt a\sqrt b[/tex] is only valid for [itex]a,b\ge0[/itex].
 
51
0
Again it raises another question.
On the basis of which statement you can say the following statement is valid-

[tex]\sqrt{ab}=\sqrt a\sqrt b[/tex] is only valid for [itex]a,b\ge0[/itex].
 
454
0
It's valid for a,b>=0 because there is a valid proof of it. this proof doesn't work if a or b can be negative. this proof uses as a definition of the square root that x is the square root of y, if x is positive and x*x = y. in that case there can be only one such number

  1. :[tex](\sqrt{ab})^2 = ab[/tex] by the definition of square root
  2. : [tex](\sqrt{a})^2 = a[/tex] by the definition of square root
  3. : [tex](\sqrt{b})^2 = b[/tex] by the definition of square root
  4. : [tex](\sqrt{ab})^2 = (\sqrt{a})^2 (\sqrt{b})^2 [/tex]
  5. : [tex](\sqrt{ab})^2 = (\sqrt{a}\sqrt{b})^2 [/tex] associativity
  6. : [tex]\sqrt{ab} = \sqrt{a}\sqrt{b} [/tex] definition of square root

the last step only works if [tex]\sqrt{ab}[/tex] and [tex]\sqrt{a}\sqrt{b}[/tex] must be positive. if this was not the case [tex]\sqrt{ab} = -\sqrt{a}\sqrt{b} [/tex] could also be possible
 

Related Threads for: Logical error

  • Last Post
Replies
10
Views
796
  • Last Post
Replies
4
Views
1K
  • Last Post
Replies
4
Views
2K
  • Last Post
Replies
3
Views
3K
  • Last Post
Replies
4
Views
1K
  • Last Post
Replies
4
Views
7K
  • Last Post
Replies
14
Views
2K
  • Last Post
2
Replies
25
Views
3K
Top